English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
0

6x-1 2x
___-___ =3
5 3

2007-09-06 12:45:01 · 2 answers · asked by bap 53 1 in Science & Mathematics Mathematics

2 answers

I presume you mean (6x-1)/5 - 2x/3 = 3

Multiply both sides by 15

3(6x - 1) - 10x = 45

Expand

18x - 3 - 10x = 45

8x - 3 = 45

8x = 48

x = 6

2007-09-06 12:50:01 · answer #1 · answered by PMP 5 · 0 0

Hi,
Well, as far as I can see your question got all discombobulated by the word processor. But, I'll take a stab at what it might be. How about this:
(6x-1)/5 -2x/3 = 3
15(6x-1)/5 -15(2x)/3 = 3(15) (Multiply by the LCD of 15.)
3(6x-1) -5(2x) = 45 (Cancell like terms in numerator and denominator.)
18x-3 -10x = 45 (Apply the distributive property.)
8x = 48 (Collect like terms on left and add 3 to each side.)
x =6

Hope my guess was right and that this helps you. Incidentally, to increase your chances of getting a correct response, preview your answers before publishing them. ;-)

FE

2007-09-06 20:51:27 · answer #2 · answered by formeng 6 · 0 0

fedest.com, questions and answers